Effects of dietary supplementation with 17-estradiol on the Steroid Hormone Levels, Gonadosomatic Index, and Gonadal Histology of Female Silver Pompano (Trachinotus blochii) Broodstock - Azizah Azizah; Munti Sarida; Yudha Trinoegraha Adiputra; Gregorius Nugroho Susanto; Agus Setyawan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Silver pompano (Trachinotus blochii) is a mariculture commodity with fast growth characteristics and easy adaptation to the environment. However, the production of its seeds is hindered by the maturation of the parent's gonads out-side the spawning season. Hormonal approaches are needed for the maturation of the parent's gonads. The aim of this study is to investigate the level of steroid hormones, gonadosomatic index, and gonad histology in female silver pompano (Trachinotus blochii) broodstock after dietary supplementation with 17-estradiol. This research is crucial for the advancement of effective and efficient techniques for rearing this fish. The study used a completely randomized design (CRD) consisting of three different 17estradiol concentrations (0 mg/kg (E1), 30 mg/kg (E2), and 60 mg/kg (E3) fed to female silver pompano broodstock for 30 days, beginning at initial feeding, each with eight individual replicates. Absolute body weight growth, steroid hormone levels, gonadal maturation index, gonadal histology, fecundity, and egg diameter of female silver pompano broodstock were all examined in this study. The incorporation of 17-estradiol hormone into the sustenance amplifies the reproductive capabilities of the female silver pompano broodstock. The inclusion of 17-estradiol hormone in the diet renders the most elevated values regarding fecundity and egg diameter in the female silver pompano broodstock. Histological examinations expose that the development of the gonads in the female broodstock treated with 17-estradiol hormone progresses towards maturation. The inclusion of 17- estradiol hormone in the diet at doses of 20 and 60 mg/kg feed yields the highest values in terms of fecundity and egg diameter in female silver pompano broodstock.Keywords:17-estradiolGonadal histologyGonadosomatic indexSteroid hormoneSilver pompano